Miracles, Hinges, and Grammar in Wittgenstein’s On Certainty - Perissinotto, Luigi (International journal for the study of skepticism, 2016)
In §513 of On Certainty Wittgenstein asks “What if something really unheard-of happened?” But with this question he is not asking us to make a forecast, a prediction, or some sort of empirico-psychological prophecy about our possible reactions. As I will attempt to show, the question regarding the unheard-of is part of Wittgenstein’s philosophical method—which is to say, it is one of the instruments with which he combats what he sees as the principal source of the confusions of philosophy: mistaking the grammatical for the empirical or, as he also says, the conceptual for the factual. In this sense the question regarding the unheard-of can shed some light on the grammatical status of what he calls “hinges.”